Al2O3/Yttria‐Stabilized Zirconia Hollow‐Fiber Membrane Incorporated with Iron Oxide for Pb(II) Removal. Issue 6 (30th April 2019) - Paiman, Syafikah Huda; Rahman, Mukhlis A; Abas, Khairul Hamimah; Abd Aziz, Azian; Ismail, Ahmad Fauzi; Hafiz Dzarfan Othman, Mohd; Jaafar, Juhana; Mohd Norddin, Mohammad Noorul Anam
Abstract: Removal by absorptive ceramic membranes can simultaneously absorb and separate metal ions from water. Alumina/yttria‐stabilized zirconia (Al2 O3 /YSZ) hollow‐fiber membranes, fabricated using phase inversion and sintering process, were deposited with iron oxide by an in‐situ hydrothermal process. The results showed that α ‐Fe2 O3 was produced and incorporated across the membranes. A reduction in flux was recorded with the deposition of α ‐Fe2 O3. However, it improved the adsorption capacity for heavy metal adsorption. The adsorption‐separation test demonstrated that the optimized membrane is able to completely remove Pb(II) ions after two hours. Abstract : Dual‐function Al2 O3 /yttria‐stabilized zirconia hollow‐fiber membranes deposited with Fe2 O3 are introduced for Pb(II) removal from wastewater. An in situ hydrothermal method is employed to simultaneously synthesize and deposit Fe2 O3 on hollow‐fiber membranes. The deposited Fe2 O3 membrane allows for the dual function of adsorption and separation for Pb(II) removal with improved adsorption capacity.